Simulation of bulk aerosol direct radiative effects and its climatic feedbacks in South Africa using RegCM4. (May 2016) - Tesfaye, M.; Botai, J.; Sivakumar, V.; Mengistu Tsidu, G.; Rautenbach, C.J.deW.; Moja, Shadung J.
Abstract: In this study, 12 year runs of the Regional Climate Model (RegCM4) have been used to analyze the bulk aerosol radiative effects and its climatic feedbacks in South Africa. Due to the geographical locations where the aerosol potential source regions are situated and the regional dynamics, the South African aerosol spatial-distribution has a unique feature. Across the west and southwest areas, desert dust particles are dominant. However, sulfate and carbonaceous aerosols are primarily distributed over the east and northern regions of the country. Analysis of the Radiative Effects (RE) shows that in South Africa the bulk aerosols play a role in reducing the net radiation absorbed by the surface via enhancing the net radiative heating in the atmosphere. Hence, across all seasons, the bulk aerosol-radiation-climate interaction induced statistically significant positive feedback on the net atmospheric heating rate. Over the western and central parts of South Africa, the overall radiative feedbacks of bulk aerosol predominantly induces statistically significant Cloud Cover (CC) enhancements. Whereas, over the east and southeast coastal areas, it induces minimum reductions in CC. The CC enhancement and RE of aerosols jointly induce radiative cooling at the surface which in turn results in the reduction of Surface Temperature (ST: up to −1 K) and Surface Sensible Heat Flux (SSHF: up to −24 W/m 2 ). The ST and SSHF decreases cause a weakening of the convectively driven turbulences and surface buoyancy fluxes which lead to the reduction of the boundary layer height, surface pressure enhancement and dynamical changes. Throughout the year, the maximum values of direct and semi-direct effects of bulk aerosol were found in areas of South Africa which are dominated by desert dust particles. This signals the need for a strategic regional plan on how to reduce the dust production and monitoring of the dust dispersion as well as it initiate the need of further research on different aspects of dust particle in South Africa. Highlights: Aerosol radiative feedbacks in South Africa have positive response on NAHR and SP. Aerosols induced elevated heat pump effect has a positive feedback on low-level CC. Bulk aerosol in South Africa has negative feedback on ST, SSHF and PBL. In terms of direct and semi-direct effects, dust have a leading role in South Africa.